Preliminary Analysis of a Wireless and Wearable Electronic-Textile EASI-Based Electrocardiogram - Teferra, Meseret N.; Hobbs, David A.; Clark, Robyn A.; Reynolds, Karen J. (Frontiers in Cardiovascular Medicine, 2021)
Background: With cardiovascular disease contining to be the leading cause of death and the primary reason for hospitalization worldwide, there is an increased burden on healthcare facilities. Electronic-textile (e-textile)-based cardiac monitoring offers a viable option to allow cardiac rehabilitation programs to be conducted outside of the hospital. Objectives: The study aimed to determine whether signals produced by an e-textile ECG monitor with textile electrodes in an EASI configuration are of sufficient quality to be used for cardiac monitoring. Specific objectives were to investigate the effect of the textile electrode characteristics, placement, and condition on signal quality, and finally to compare results to a reference ECG obtained from a traditional Holter monitor. Methods: ECGs during different body movements (yawning, deep-breathing, coughing, sideways, and up movement) and activities of daily living (sitting, sitting/standing from a chair, and climbing stairs) were collected from a single participant using a novel e-textile ECG and a reference Holter monitor. Each movement or activity was recorded for five minutes with two-minute intervals between each recording. Three different textile area electrodes (40mm2, 60mm2, and 70mm2) and electrode thicknesses (3mm, 5mm, and 10mm) were considered in the experiment. The effect of electrode placement within the EASI configuration was also studied. Results: The overall signal quality from the 70mm2 textile electrodes was higher compared to the smaller area electrodes. Results showed that the ECGs from 3mm and 5mm textile electrodes showed good quality. Regarding location, placing the 'A' and 'I' electrodes on the left and right anterior axillary points, respectively, showed higher signal quality compared to the standard EASI electrode placement. Wet textile electrodes showed better signal quality compared to their dry counterparts. When compared to the traditional Holter monitor, there was no significant difference in signal quality. Conclusion: The e-textile EASI ECG monitor could be a viable option for real-time monitoring of cardiac activities. A clinical trial is recommended to validate the results in a clinical population.